Raciocínio combinatório: uma proposta para professores de matemática do ensino fundamental anos finais - Gerdenits, Gisele Aparecida Massuela (2014)
This research has as main objective making a manipulative material to work sequences of activities by introducing the notion of Combinatorial Analysis in an intuitive and natural way in elementary school final years. Without using formulas, it presents an encouragement to use the Multiplicative Principle, tree diagram and list of possibilities as an important tool for solving various problems. We started the research making a description of the current curriculum documents in the Department of Education of the State of São Paulo, followed by historical overview and theoretical foundation. The survey was developed with the implementation of three activities with students from the 5th grade - 6 year to 8th grade - 9th year of elementary school in a Public State School in the city of Sorocaba/SP. These activities were designed to find out the students difficulties in the development of problems involving Combinatorial reasoning and to propose manipulative materials at low cost and to help in the construction and understanding of that content, since a big part of students and teachers consider it difficult to understand. These manipulative materials represent the final product of this research and it is hoped that teachers use them in their classrooms to make their classes more dynamic, rich and arousing the interest of the students.